THE STRENGTHENING OF SUNDANESE LOCAL WISDOM THROUGH LITERATURE IN PURWAKARTA JAWA BARAT - Ella Janawati Sundari; Anna Nur Anisa; Nai Supartini (IKIP Siliwangi, 2019)
Local wisdom is the using of culture’s elements based on regionalism. In Purwakarta society, this local wisdom is highly held especially because there is a rule from regional government which requires their society to revert to their ancestor’s cultures. The one of the local wisdomelement which is applied in Purwakarta is literature. Sunda language is the language they used in heir daily communication.This research describes the strengthening of Sundanese local wisdom through literature especially the using of Sundanese in every Wednesday either in regional institutions or in schools in Purwakarta. The name of Sunda for Sunda ethnic has some meanings which refers to hope of the kindness in all aspects of life. The writers choose Purwakarta because the writers are interested in the culture of Purwakarta. The writers want to know how the culture in Purwakarta develop. The culture basically remain nuanced sundanese cultural and religious values especially Islam. the acculturation of Sunda and Hindu culture, and the use of traditional language and writing or traditional literature in daily life. This research usedis qualitative method with case study design. The result of this research shows that the using of Sundanese in every Wednesday is very effective in strengthening Sundanese local wisdom.